Genetic investigation of Italian domestic pigeons increases knowledge about the long-bred history of Columba livia (Aves: Columbidae). Issue 2 (2nd April 2016) - Bigi, D.; Mucci, N.; Mengoni, C.; Baldaccini, E. N.; Randi, E.
Abstract: In this study, we aimed to characterise the genetic diversity of Italian pigeon breeds and describe the relationships among them and other European lineages, conjecturing which processes have led to actual breeds. We analysed the eight most diffused Italian pigeon breeds in addition to 11 foreign lineages that could have shared common ancestors or have been used in the creation of the Italian breeds. We analysed 12 autosomal microsatellite loci in 427 samples collected from 19 breeds belonging to six main groups of domestic pigeons (tumblers and highflyers, structure, owls, wattle, utility and hen). Genetic variability did not differ considerably among breeds, with an average observed heterozygosity ( H O ) of 0.550 ± 0.072 (max = 0.661 in breed Sottobanca; min = 0.411 in breed Frillback). The 21.34% of total genetic variation found was partitioned among breeds. Italian pigeon breeds were assigned coherently to their respective groups of origin. The analysis supports the origin of homing pigeons from English Carrier and the existence of a close relationship between Old Dutch Capuchine and Italian Owl. Despite the differences in body size, pigeons of the breeds belonging to the hen group are genetically very similar. The sub-populations recognised by breeders inside Italian Owl and Triganino are not genetically supported and their identification as new breeds ought not to be yet proposed, although they are morphologically distinguishable. Consequently, it could also be discussed how the genetic characterisation of domestic lineages could give useful information in breeding and selection processes.